O ensino de literatura no cursinho pré-vestibular DACA - Toscano, Mariela Fonseca [UNESP]; Santos Neto, Otavio Marino dos [UNESP]; Soubhia, Ana Maria Pires [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The concept and the importance of literature in today's society has been highly regarded, especially when it comes to their influence in the lives of young people. Thus, the literary mode receives a special focus on the pre-entrance exam preparatory course DACA, an extension project linked to UNESP, campus of Araçatuba. The project assists students who are not able to fund a study in private schools to enroll in universities and more than that, it also has the objective of social and cultural education of young people. The "Word Art" as is conceptualized literature, gaining more space in the classroom and in the interest of our students. The purpose of this paper is to describe didactic forms found to arouse students' interest in literature through reading and also by other art media such as music, movies and theater. Thus, develops the content of the exam of a closely the reality of young people and emphasizes the social importance of artistic expression in the sociocultural growth.

O conceito e a importância da literatura na sociedade atual têm sido muito considerados, principalmente quando se trata de sua influência na vida dos jovens. Dessa maneira, a modalidade literária recebe um foco especial no cursinho pré- vestibular DACA, um projeto de extensão vinculado à UNESP, no campus de Araçatuba. O projeto auxilia alunos que não têm condição de custear um estudo em colégios particulares à ingressarem nas universidades e mais do que isso, possui também o objetivo de formação social e cultural dos jovens. A “arte da palavra”, como é conceituada a literatura, ganha cada vez mais espaço na sala de aula e no interesse dos nossos alunos. A proposta deste trabalho é descrever formas didáticas encontradas para despertar o interesse dos estudantes pela literatura através da leitura e também por outros meios de arte como a música, filmes e teatro. Assim, desenvolve-se o conteúdo do vestibular de uma maneira próxima a realidade dos jovens e enfatiza à importância social da manifestação artística no crescimento sociocultural.
Keywords: Literature; Education; Entrance exam; Literatura; Ensino; Vestibular